The Bridge - Kapustin, Petr (project baikal, 2021)
The bridge is a popular image of formation of the city’s symbol, brand and composite character. The essay proposes interpretation of the mythopoetics of bridges, one of the most ambiguous, mysterious and attractive typological niches in architecture.
Keywords: bridge; mythopoetics of architecture; architectural image; image of the city; sense and meaning in architecture